2007
DOI: 10.1007/s10593-007-0085-y
|View full text |Cite
|
Sign up to set email alerts
|

Acylation of perimidine with 1,3,5-triazines in polyphosphoric acid

Abstract: The use of 1,3,5-triazines 2 as formylating agents in the presence of a Lewis acid has been reported [1]. The use of substituted 1,3,5-triazines as acylating agent was not known. We have shown that formylation of perimidine 1 does not occur under these conditions. Formylation has been successfully carried out with a threefold excess of 1,3,5-triazine 2 in 80% PPA (4 g per mmol of perimidine) at 55-60°C for 1 h. The yield of perimidine-6(7) carbaldehyde (3a) was 91% under these conditions. The compound was sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 3 publications
(5 reference statements)
0
8
0
Order By: Relevance
“…We have already shown that the 1,3,5-triazine-PPA* system is useful for the acylation and formylation of perimidines [2] and the synthesis of 1,2,3,7-tetraazapyrenes from 1H-naphtho[1,8-de][1,2,3]triazine (1,2,3-triazaphenalene) [3]. The present study is a continuation of our investigation of the synthetic scope of this system.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…We have already shown that the 1,3,5-triazine-PPA* system is useful for the acylation and formylation of perimidines [2] and the synthesis of 1,2,3,7-tetraazapyrenes from 1H-naphtho[1,8-de][1,2,3]triazine (1,2,3-triazaphenalene) [3]. The present study is a continuation of our investigation of the synthetic scope of this system.…”
mentioning
confidence: 59%
“…Since perimidines [2] and 1,2,3-triazaphenalene [3] undergo, in effect, double electrophilic attack by the system of 1,3,5-triazines 2 in PPA, we might have assumed that perimidines 1 would react analogously. Indeed, 1,3,7-triazapyrenes 3a-d were obtained in 50-65% yield upon heating 1a-d with 1,3,5-triazine (2a) in PPA.…”
mentioning
confidence: 99%
“…Aromatization of 47 takes place by elimination of the amidine, which undergoes hydrolysis during isolation. As established somewhat earlier, at a lower temperature the perimidines are formylated (acylated) in the 1,3,5-triazine-PPA system as a result of hydrolysis of intermediates of the 46 type or their precursors [47] during isolation. This confirms indirectly the mechanism proposed for the formation of 1,3,7-triazapyrenes from perimidines.…”
Section: Triazapyrenesmentioning
confidence: 70%
“…The method of acylation (formylation) of perimidines, which we developed [1], is based on their reaction with 1,3,5-triazine in PPA (polyphosphoric acid). However, addition of sodium nitrite to the reaction mixture unexpectedly led to a change in the direction of the process.…”
mentioning
confidence: 99%
“…The nitroso compound 4 is then acylated with triazine 2 to give the nitroso compounds 5 which form the pentacyclic compounds 6, which are converted to the tetraazapyrenes 3a,b. 1 …”
mentioning
confidence: 99%